F-doped nickel cobalt oxide-carbon composite electrocatalysts paired with mechanically robust anion-conducting chitosan membranes for flexible and rechargeable zinc-air batteries - Kurian, Maria; Ranganath, Suresha P.; Vijayakumar, Vidyanand; Sivadasan, Sneha; Kurian, Rachna Maria; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Energy Materials, 2024)
High-performing, cost-effective electrocatalysts and anion-conducting polymer electrolyte membranes are essential for realizing commercially affordable zinc-air batteries (ZABs). In this context, the present work deals with the development of a bifunctional electrocatalyst and an anion-exchange quasi-solid-state electrolyte membrane (based on quaternary ammonium group-grafted chitosan) for demonstrating flexible and rechargeable ZABs. The electrocatalyst composed of NiCoO2 nanoparticles supported on a carbon framework showcased substantial advancements in its ability to catalyze both oxygen reduction and evolution reactions (ORR and OER) due to the heteroatom doping by fluorine. For instance, the optimized electrocatalyst (F-NCO-ADC-600) exhibited an onset potential of 0.96 V vs RHE with a half-wave potential of 0.83 V vs RHE for ORR, a comparable performance with the state-of-the-art Pt/C (1.0 and 0.86 V vs RHE, respectively). On a similar note, the same catalyst also displayed an overpotential of 340 mV vs RHE for OER at a current density of 20 mA cm(-2), close to that of a standard RuO2 catalyst (337 mV vs RHE). In the context of polymer electrolytes, the quaternary ammonium-group-grafted chitosan membrane depicted superior ionic conductivity, liquid electrolyte uptake, and mechanical properties, thereby proving to be an efficient anion-conducting polymer electrolyte membrane. The realistic application of the developed electrocatalyst and the polymer electrolyte membrane is demonstrated in the ZAB prototypes. The assembled rechargeable ZAB (RZAB) delivered a power density of 207 mW cm(-2) and maintained high-rate capability and cycling stability, notably in a flexible configuration (f-RZABs). Thus, this work provides a strategy for the rational design of anion-exchange membranes and bifunctional electrocatalysts for f-RZABs.
Keywords: anion-conducting polymer electrolytemembrane; F-doping; flexible and rechargeable zinc-air batteries(f-RZABs); oxygen evolution reaction(OER); oxygen reduction reaction (ORR)

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte